The Imperceptibility of Individuation. "Deleuze and Guattari Studies" and the Problem of Becoming - Kłos-Czerwińska, Paulina (Sensus Historiae, 2025)
The research objective of the article is to find out and present the ways that subjects undertake to perform their internal life. The inherent part of this life is in the sphere called by Deleuze the sphere of intensities. Dramatization of such intensities creates certain matrices of thinking and feeling. After the transference of these intensities onto the surface of discourse they become the objectivities of experience and become included into the repertoire of the internal life of the subject. The article is an attempt to present in details such a version of subjective individuation.